Next generation gender research: Looking back to inform the future - Njuki, Jemimah (International Development Research Centre, 2018)
Presented by Jemimah Njuki (IDRC), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.